Ragam Kisah Sihir dalam al-Qur’an: dari Harut-Marut Hingga Turunnya Surah al-Mu’awwidhatain - Mujahidin, Muhammad Saekul (Tasamuh: Jurnal Studi Islam, 2024)
Magic is a science that is related to black magic and is also related to the evil within a person, the occult has emerged for a long time even for a very long time and will remain until the end of time. in writing stories of magic in the Qur'an the author divides into three events that occur in the Qur’an, among others; First, the story of Harut and Marut has many different versions, but in this incident the two characters are closely related to witchcraft, the second is the story of Moses fighting a shaman from Pharaoh, where Moses was able to defeat the magic snake belonging to the shaman from Pharaoh with a miracle from God, the third is the story of al-Mu’auwwidzatain (al-falaq and an-Nas), namely when Ifrit from the jinn group, once tried to harm the Prophet Muhammad with his tricks. Many commentators argue that the two letters were revealed because the Prophet Muhammad was tested in the form of magic by the Jews, namely Labid bin al-A’sham.